A 3D Multifunctional Architecture for Lithium–Sulfur Batteries with High Areal Capacity. Issue 6 (19th April 2018) - Zhao, Shiyong; Fang, Ruopian; Sun, Zhenhua; Wang, Shaogang; Veder, Jean‐Pierre; Saunders, Martin; Cheng, Hui‐Ming; Liu, Chang; Jiang, San Ping; Li, Feng
Abstract: Lithium–sulfur (Li–S) batteries are highly attractive as next‐generation electrochemical energy‐storage technologies because they can provide a high energy density at a low cost. However, the performance degradation of sulfur cathodes with high mass loadings remains a significant challenge to be addressed. Here, a 3D multifunctional integrated and sponge‐like architecture is designed as the cathode framework, which provides a favorable balance between high sulfur loadings and uncompromised electrochemical performances. In this architecture, a highly porous nitrogen‐doped carbon fiber foam is used as a 3D current collector and host for sulfur accommodation and a thin graphene layer is used for polysulfide interception, which not only facilitates fast electron and lithium‐ion transport but also enables effective active material immobilization by both physical restriction and chemical adsorption. With a sulfur loading of 7.7 mg cm −2, high areal capacities up to 8.7 mAh cm −2 are attained together with excellent cycling stability over 500 cycles. This approach demonstrates a new concept for the construction of cathode architectures for practical Li–S batteries and can be extended to other battery systems. Abstract : A 3D multifunctional integrated and sponge‐like architecture is designed as the cathode framework for lithium–sulfur batteries, which provides a favorable balance between high sulfur loadings and uncompromised electrochemical performances. With a sulfur loading of 7.7 mg cm −2, high areal capacities up to 8.7 mAh cm −2 are attained together with excellent cycling stability over 500 cycles.